The medication for pneumocystis pneumonia with glucose-6-phosphate dehydrogenase deficiency patients - Zhang, Ziyu; Li, Qinhui; Shen, Xiaoyan; Liao, Lankai; Wang, Xia; Song, Min; Zheng, Xi; Zhu, Yulian; Yang, Yong (Frontiers in Pharmacology, 2022)
Pneumocystis pneumonia (PCP) is an opportunity acquired infection, which is usually easy to occur in patients with AIDS, organ transplantation, and immunosuppressive drugs. The prevention and treatment must be necessary for PCP patients with immunocompromise. And the oxidants are currently a typical regimen, including sulfanilamide, dapsone, and primaquine, etc. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked gene-disease that affects about 400 million people worldwide. The lack of G6PD in this population results in a decrease in intracellular glutathione synthesis and a weakening of the detoxification ability of the oxidants. As a result, oxidants can directly damage haemoglobin in red blood cells, inducing methemoglobin and hemolysis. When patients with G6PD deficiency have low immunity, they are prone to PCP infection, so choosing drugs that do not induce hemolysis is essential. There are no clear guidelines to recommend the drug choice of this kind of population at home and abroad. This paper aims to demonstrate the drug choice for PCP patients with G6PD deficiency through theoretical research combined with clinical cases.